2017
DOI: 10.1080/14740338.2017.1358361
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential for using drug indications to prevent look-alike and sound-alike drug errors

Abstract: Including the FDA-approved indication in the drug prescription may be used to differentiate LASA drug pairs and thus, prevent wrong drug medication errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…[3][4][5]21,[24][25][26][27] To our knowledge, only 2 other studies have indirectly evaluated the associations of matching medication product attributes on SALA confusion. 16,17 Both studies explored the associations of SALA confusion with generic name, therapeutic class, health problem, or medication indication. They found that a substantial proportion of SALA medication pairs shared the same indications or belonged to the same therapeutic class.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5]21,[24][25][26][27] To our knowledge, only 2 other studies have indirectly evaluated the associations of matching medication product attributes on SALA confusion. 16,17 Both studies explored the associations of SALA confusion with generic name, therapeutic class, health problem, or medication indication. They found that a substantial proportion of SALA medication pairs shared the same indications or belonged to the same therapeutic class.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results of this study were presented at the American Pharmacist Association's Annual Meeting (March [16][17][18][19]2018; Nashville, TN) in the form of a poster presentation.…”
Section: Authors' Notementioning
confidence: 99%
See 1 more Smart Citation
“…The investigations on medication errors have discovered some critical topics like awareness of confused drugs and control of high-risk drugs. The confused drugs, including look-alike, sound-alike (LASA) name pairs, are a critical group for medication errors 4 . LASA covers medications with visual similarities in physical appearance, packaging, and/or name (in the form of spelling and/or phonetics).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the incidence of and approaches to preventing medication errors has become a subject of growing importance in medical and pharmaceutical sciences [37][38][39][40][41]. It has been shown that the occurrence of inappropriate medication use can be linked not only to name confusion [42,43] but also, most notably, to labelling and packaging confusion [44][45][46]. Specifically, past research offers insights into the mechanisms of how labelling and final packaging influence the ability to accurately recognize medicines [25,47,48].…”
Section: Introductionmentioning
confidence: 99%